Originally Posted by

**algorithm** Hi,

y''(t) + 3y'(t) + y(t) = 2x(t)

Where x(t) = u(t), and the system is initially at rest. We are interested only when t>=0, so x(t) = 1 always.

I can solve it by Laplace transforms:

Original eqn:

y''(t) + 3y'(t) + y(t) = 2

Taking Laplace of both sides (and assuming system was at rest):

Y(s)[s^2 + 3s + 2] = 2/s

Y(s) = [2/s]/[s^2 + 3s + 2]

Y(s) = A/s + B/(s + 1) + C/(s + 2)

Finally: y(t) = 1 - 2exp[-t] + ext[-2t]

--------

The problem is when I try solving it by equating coefficients. I get a different answer:

Original eqn:

y''(t) + 3y'(t) + y(t) = 2

To get complementary function, y_comp(t):

y''(t) + 3y'(t) + y(t) = 0

Auxiliary eqn: s^2 + 3s + 1 = 0; s = -1, -2

y_comp(t) = Aexp[-t] + Bexp[-2t]

To get particular integral, y_pt(t):

Forcing function: x(t) = 1

Gives y_pt(t) = 1

General solution:

y(t) = y_comp(t) + y_pt(t) = Aexp[-t] + Bexp[-2t] + 1

Solving for the constants A and B (problem is here):

y'(t) = -Aexp[-t] -2Bexp[-2t]

y''(t) = Aexp[-t] + 4Bexp[-2t]

Given the system was at rest, I get:

0 = -A - 2B (1)

0 = A + 4B (2)

Solving these gives A=B=0. But this means that y(t) = 1, which is different to the Laplace solution of y(t) = 1 - 2exp[-t] + ext[-2t].

Thanks for any help.